2022
DOI: 10.5935/1518-0557.20210047
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 21 and Assisted Reproductive Technologies: A review

Abstract: Trisomy 21 is the most common genetic disorder seen among infants, and it causes spontaneous abortions, abnormal neural development and other pathologies associated with newborn development. In newborns with this trisomy, 90-95% have full trisomy, 1.4-1.9% have mosaicism, and 1-4.7% have translocations. The principal cause of trisomy 21 is advanced maternal age, in which recombination errors may occur during fetal development, age-related accumulation of damaged DNA, cohesin degradation producing the premature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 162 publications
0
8
0
2
Order By: Relevance
“…Actually, it is hypothesized that a great part of idiopathic infertility cases would have an epigenetic origin, being more frequent than the exclusive genetics ones [ 22 , 29 , 45 ]. It is worth highlighting that the shorter latency period of the spermatozoa compared with the oocyte makes the probability of gaining epigenetic modifications smaller [ 23 , 46 ]. The main roles of epigenetics in sperm functions and how they can be altered are discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, it is hypothesized that a great part of idiopathic infertility cases would have an epigenetic origin, being more frequent than the exclusive genetics ones [ 22 , 29 , 45 ]. It is worth highlighting that the shorter latency period of the spermatozoa compared with the oocyte makes the probability of gaining epigenetic modifications smaller [ 23 , 46 ]. The main roles of epigenetics in sperm functions and how they can be altered are discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…We conducted further follow-up and found that although fetal malformations or RSA could not be diagnosed prior to IVF, there must have been some specific reasons for choosing IVF, such as older maternal age, biochemical pregnancy or only one case of embryonic arrest, and untested aborted tissue. In addition to the IVF process itself, ovarian stimulation and cryopreservation are potential factors contributing to fetal aneuploidy [ 17 , 18 ] and we must acknowledge that the aforementioned confounding factors were not controlled for in this study and it was difficult for us to do so. There is no doubt that the rapid development of ART has solved many fertility problems.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of genetic imbalance has been widely reported for over a century, describing the phenomenon that changing the dosage of individual chromosomes or large chromosomal segments (aneuploidy) has more severe effects on the phenotype than changing a whole set of chromosomes in a genome (ploidy) (Birchler and Veitia, 2012, 2021). In human, only trisomies 13, 18, and 21 of the entire autosomal aneuploidies can survive to birth, while only trisomy 21 can survive to adulthood (Orr et al, 2015; Sanchez-Pavon et al, 2021). This fact may be related to the size of chromosomes or the number of genes contained, with chromosome 21 encoding the fewest genes and causing the least global disruption of gene expression.…”
Section: Discussionmentioning
confidence: 99%